1989
DOI: 10.1007/bf00261154
|View full text |Cite
|
Sign up to set email alerts
|

A full length cDNA clone for the alkaline protease from Aspergillus oryzae: Structural analysis and expression in Saccharomyces cerevisiae

Abstract: We have cloned and determined the nucleotide sequence of a cDNA fragment for the entire coding region of the alkaline protease (Alp) from a filamentous ascomycete Aspergillus oryzae. According to the deduced amino acid sequence, Alp has a putative prepro region of 121 amino acids preceding the mature region, which consists of 282 amino acids. A consensus sequence of a signal peptide consisting of 21 amino acids is found at the N-terminus of the prepro region. The primary structure of the mature region shares e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…The N-terminal amino acid sequence revealed a homology of 88% with the sequence of the alkaline proteinase "Alp" of A. oryzae, a typical serine proteinase of the subtilisin-type. 28 We also observed 39% homology with proteinase-K from Tritirachium album. 29 The relationship to proteinase-K is also reflected by the relative resistance of Alp to sodium dodecyl sulphate; however, Alp hydrolysed the 4-nitroanilide of arginine, whereas proteinase-K did n0t.l' There was no evidence for disulphide bonds in Alp, which is in agreement with the related enzyme of A. oryzae,28 whereas proteinase-K has two cyst in^.^^ Alp was found to possess slight elastinolytic activity, and it may be related to the elastase of A. fumigatus, which was described previo~sly.~~ 26 The elastinolytic and caseinolytic activity of this enzyme proved to be inseparable, and the final purification product, examined by SDS-PAGE under reducing conditions, consisted of three molecular species of mol.…”
Section: Discussionmentioning
confidence: 57%
“…The N-terminal amino acid sequence revealed a homology of 88% with the sequence of the alkaline proteinase "Alp" of A. oryzae, a typical serine proteinase of the subtilisin-type. 28 We also observed 39% homology with proteinase-K from Tritirachium album. 29 The relationship to proteinase-K is also reflected by the relative resistance of Alp to sodium dodecyl sulphate; however, Alp hydrolysed the 4-nitroanilide of arginine, whereas proteinase-K did n0t.l' There was no evidence for disulphide bonds in Alp, which is in agreement with the related enzyme of A. oryzae,28 whereas proteinase-K has two cyst in^.^^ Alp was found to possess slight elastinolytic activity, and it may be related to the elastase of A. fumigatus, which was described previo~sly.~~ 26 The elastinolytic and caseinolytic activity of this enzyme proved to be inseparable, and the final purification product, examined by SDS-PAGE under reducing conditions, consisted of three molecular species of mol.…”
Section: Discussionmentioning
confidence: 57%
“…Homology comparison of the deduced amino acid sequence of Eap with other known proteins indicated that the gene encode an extracellular protease that belongs to the serine peptidase family S8 (Clan SB; Sub family S8A); EAP was found to be translated as a precursor protein and it is assumed that the E. album protease undergoes two processing events: One after amino acid 21 to remove the signal peptide and the second after amino acid 108 to remove the propeptide and thereby releasing the mature enzyme (molecular weight *29 kDa). The putative propeptide region next to the signal peptide functions by binding to the enzyme active site as an inhibitor and is required for proper folding and secretion of the enzyme (Tatsumi et al 1989;Yabuta et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The AlPase activity was measured on azocollagen at different pH values in citrate buffer (50 mM, pH 4-7), in Tris-HC1 buffer (50 mM, pH 6-10) and in glycineNaOH buffer (100 mM, pH [8][9][10][11][12]. Activities measured at the same pH with different buffers were identical.…”
Section: Proteolytic Assaysmentioning
confidence: 99%